Shopping i Stockholm Sociala praktiker på gatunivå, 1700-1850 - Hellsing, My; Ilmakunnas, Johanna (Kriterium, 2023)
When Anna Johanna Grill travelled from Sweden to England in 1788, she was impressed by the vast array of consumer goods in shops. In her travel diary, she writes how the shopkeepers displayed goods in myriad of ways that fooled people into shopping. How did shops look like in Anna Johanna Grill's hometown Stockholm in the eighteenth century and the early nineteenth century? Were there distinctive shopping streets? Who sold goods, who shopped them and what goods were available? How were goods displayed in shops and marketed? How households act in organising their purchases and consumption? From a microhistorical case studies, this richly illustrated anthology widens the perspective to social, economic and cultural practices in everyday urban life. The chapters demonstrate how shopping streets and shops with their range of silk fabrics, accessories, fashion plates, blacksmithing, wigs and hair pomades not only met the desires of consumers, but also enabled dreams of novel identities and social accession for themselves and their families.